Capsanthin inhibits migration and reduces N-linked glycosylation of PD-L1 via the EZH2-PD-L1 axis in triple-negative breast cancer brain metastasis - Yi-Chung Chien; Jia-Yan Wu; Liang-Chih Liu; Yung-Luen Yu (Cell Death Discovery)
Abstract Breast cancer metastasis to the brain, occurring in about 15–25% of cases, represents a major obstacle in the treatment of triple-negative breast cancer (TNBC). The molecular mechanisms driving this form of metastasis are still largely unknown. PD-L1, an immune checkpoint protein, is central to tumor immune evasion and has become a focus for immunotherapy development. While PD-L1 inhibitors have shown success in various cancer types, their effectiveness in TNBC brain metastases remains to be fully investigated. This highlights the urgent need to understand the complex interactions between metastatic brain tumors and the tumor microenvironment in TNBC patients. Gaining insights into these dynamics is crucial for developing new targeted therapies, including those that modulate the PD-L1 pathway, to better manage and treat TNBC brain metastases. We explore the impact of Capsanthin on the tumor microenvironment of brain metastases in triple-negative breast cancer (TNBC). Our results reveal that Capsanthin effectively inhibits the migration of brain metastasis TNBC cells. Furthermore, Capsanthin significantly reduces the expression of EZH2 and N-linked glycosylated PD-L1 proteins and mRNA in TNBC cells, encompassing both primary and metastatic sites, as well as in mesenchymal stem cells (3A6). Data from The Cancer Genome Atlas (TCGA) indicate that elevated expression levels of EZH2 correlate with poorer patient prognosis. Immunoprecipitation assays demonstrate a direct interaction between EZH2 and PD-L1 in brain metastases of TNBC, underscoring the pivotal role of the EZH2-PD-L1 axis. Additionally, Capsanthin was found to suppress the expression of epithelial-mesenchymal transition (EMT) markers in metastatic brain TNBC cells and mesenchymal stem cells. Our results suggest that Capsanthin can modulate the tumor microenvironment and inhibit key pathways involved in cancer progression, offering potential therapeutic benefits for patients with TNBC brain metastases.